Work From Home: Measuring Work Life Balance, Job Burnout and Employee Happiness for Startup Company Employees in Jakarta - Jeshica khoirunnisa Amalia; Parwoto Parwoto (Journal Research of Social Science, Economics, and Management, 2022)
The COVID-19 pandemic has changed the way people live and work, and the way industry and organizations operate. The most obvious change is in a situation where organizational activities start running remotely, or what is known as a work from home policy. The COVID-19 pandemic has brought shocks to the economic situation and social conditions of people around the world. Working from home affects work-life balance, work fatigue, and also employee happiness. This research is included in the type of quantitative research with a focus on employees of startup companies in Jakarta with a total of 65 respondents. Data was collected using a questionnaire which was then analyzed using SmartPLS 3.3.7 software. Based on the results of this study indicate that work from home has a significant positive effect on work-life balance and employee happiness, as well as a significant negative effect on job burnout.